2021
DOI: 10.1093/ajcn/nqab288
|View full text |Cite
|
Sign up to set email alerts
|

Whole-fat dairy products do not adversely affect adiposity or cardiometabolic risk factors in children in the Milky Way Study: a double-blind randomized controlled pilot study

Abstract: Background Limited evidence supports the common public health guideline that children >2 y of age should consume dairy with reduced fat content. Objectives We aimed to investigate the effects of whole-fat compared with reduced-fat dairy intake on measures of adiposity and biomarkers of cardiometabolic risk in healthy 4- to 6-y-old children. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Associate Professor Therese O'Sullivan (Edith Cowan University) highlighted findings from the Milky Way study, a double-blind randomised controlled trial in forty-nine healthy children aged 4 to 6 years who consumed whole-fat dairy or reduced-fat products for 3 months. The results of this pilot study showed no significant differential changes in energy intake or markers of adiposity or cardiometabolic disease risk, suggesting the reduced-fat dairy products do not have health advantages over whole-fat dairy for children (7,8) . Professor Ian Givens (University of Reading) then raised the question of potentially unnecessary restriction of dairy products in the diet due to their high-saturated fat content and therefore increased risk of CVD (9) .…”
Section: Other Special Symposiums and Sessionsmentioning
confidence: 75%
“…Associate Professor Therese O'Sullivan (Edith Cowan University) highlighted findings from the Milky Way study, a double-blind randomised controlled trial in forty-nine healthy children aged 4 to 6 years who consumed whole-fat dairy or reduced-fat products for 3 months. The results of this pilot study showed no significant differential changes in energy intake or markers of adiposity or cardiometabolic disease risk, suggesting the reduced-fat dairy products do not have health advantages over whole-fat dairy for children (7,8) . Professor Ian Givens (University of Reading) then raised the question of potentially unnecessary restriction of dairy products in the diet due to their high-saturated fat content and therefore increased risk of CVD (9) .…”
Section: Other Special Symposiums and Sessionsmentioning
confidence: 75%
“…However, a previous study examined the percentage of children and adolescents who consumed different types of milk and found that more than 60 percent of children and adolescents chose low-fat or skim milk, and most overweight individuals did not choose whole milk [ 84 ]. In addition, a latest double-blind randomized study showed that whole milk intake does not increase the risk of obesity [ 85 ]. Therefore, the effect of fat in milk on obesity is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance was estimated using HOMA-IR calculated as fasting insulin [µU/ml] × fasting glucose [mmol/L]/22.5). Fatty acids were measured in erythrocytes that were collected and stored at −80 o C until assay [ 20 ]. Plasma leptin and adiponectin were measured in plasma stored at −80 o C using Quantitkine ELISA kits for Human Leptin and Human Total Adiponectin/ Arcp30, respectively (R&D systems Inc, Minniapolis USA).…”
Section: Methodsmentioning
confidence: 99%